The Variation of West Sulawesi Dialects Used in STAIN Majene - Uswatunnisa Uswatunnisa; Afredy Krismahuddin; Khairunnisa Khairunnisa (Madrasah Tsanawiyah DDI Cilellang, 2021)
Dialect is a substandard or basic standard of the dialect itself which is also often associated with language, especially the spoken language in certain region. The researchers were interested to observe how vary the dialects used. The purpose of this research was to find out dialects' variation used during teaching and learning process of Speaking class in STAIN Majene. STAIN Majene is the newest university located in Majene regency, West Sulawesi province in which it is not the capital of the province. Yet, STAIN Majene students were coming from many different places and backgrounds. The methods used in the research were spoken data recording, place and the spoken language observation at the university. The researchers found that Mandarese is still the dominant dialect used in STAIN Majene area due to the students and non-students such as lecturers are mostly originally come from Majene and Polewali Mandar regencies.